Gut Feelings: How Microbes, Diet, and Host Immunity Shape Disease - Benjamin Frederick Theis; Jun Sung Park; Jong Sung Anthony Kim; Sareh Zeydabadinejad; Matam Vijay-Kumar; Beng San Yeoh; Piu Saha (Biomedicines)
The human gut microbiome is intricately linked to systemic and organ-specific immune responses and is highly responsive to dietary modulation. As metagenomic techniques enable in-depth study of an ever-growing number of gut microbial species, it has become increasingly feasible to decipher the specific functions of the gut microbiome and how they may be modulated by diet. Diet exerts both supportive and selective pressures on the gut microbiome by regulating a multitude of factors, including energy density, macronutrient and micronutrient content, and circadian rhythm. The microbiome, in turn, contributes to local and systemic immune responses by providing colonization resistance against pathogens, shaping immune cell activity and differentiation, and facilitating the production of bioactive metabolites. Emerging research has strengthened the connections between the gut microbiome and cardiometabolic disorders (e.g., cardiovascular disease, obesity, type-2 diabetes), autoimmune conditions (e.g., type-1 diabetes, rheumatoid arthritis, celiac disease), respiratory disease, chronic kidney and liver disease, inflammatory bowel disease, and neurological disorders (e.g., Alzheimer’s, Parkinson’s disease, depressive disorders). Here, we outline ways in which dietary factors impact host response in diseases through alterations of gut microbiome functionality and composition. Consideration of diet-mediated microbial effects within the context of the diseases discussed highlights the potential of microbiome-targeted treatment strategies as alternative or adjunct therapies to improve patient outcomes.